Evolution of the prevalence and incidence of oral disorders in Portugal, 1990–2016: findings from the Global Burden of Disease 2016 Study. (29th March 2019) - Pereira, Gonçalo Martins; Oliveira, Pedro; Taveira, Nuno
Abstract : Introduction: Oral disorders are highly prevalent worldwide and remain a major public health challenge [1 ]. In addition to the increasing burden associated with these disorders, there has been an increase in their direct treatment costs and productivity losses [2 ]. The Global Burden of Disease (GBD) Study goals are to provide up-to-date estimates for descriptive epidemiology, such as information on disease prevalence, incidence and severity, nationally and globally, since 1990 [1 ]. The aim of this study is to present the prevalence and incidence of oral disorders in Portugal since 1990. Materials and methods: Data was retrieved from the GBD Study 2016, coordinated by the Institute for Health Metrics and Evaluation (IHME) and from national databases. Case definitions followed the WHO definitions for dental caries, periodontal diseases and severe tooth loss. Detailed methods are described elsewhere [1 ]. Results: Oral disorders are extremely prevalent in the Portuguese population since 1990, affecting 60% of the population. In the past 26 years there has been a decrease in the prevalence of these disorders in the population younger than 50 years (1990 – 3.562.046, 29/2016 – 3.168.985, 21) and an increase in the population older than 50 years (1990 – 2.073.072, 95/2016 – 2.915.942, 16). Within the latter population the prevalence is higher in the individuals aged between 50 and 69 (1990 – 1.435.368, 04/2016 – 1.828.081, 43). Except for the population <5 years, prevalence is always higher in females than males in all age intervals. Between 1990-2016, for all ages, incidence was always higher than prevalence, despite following the same trend, with growing incidences for the population older than 50 years. Discussion and conclusions: The prevalence and incidence of oral disorders in Portugal follow the same trend observed globally [1 ]. The rising prevalence and incidence of oral disorders seen in the older population should be the focus of public health interventions since it is associated with a significant burden and is a risk factor for several systemic diseases, such as cardiovascular diseases and diabetes [3 ]. If no measures are taken, the expected increase of the Portuguese geriatric population will most likely reflect a continuous increase in oral disorders.